2017
DOI: 10.1177/000313481708300842
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Mastectomy and Lumpectomy in Octogenarians and Nonagenarians with Early-Stage Breast Cancer

Abstract: Prospective studies have shown equal outcomes after mastectomy or breast conservation in patients with invasive breast cancer; however, many of these studies excluded elderly patients. We identified patients in their eighties and nineties with clinical stage 0 to II breast cancer undergoing mastectomy or lumpectomy with or without radiation from the prospective sentinel lymph node database at Wake Forest Baptist Health and analyzed their treatment and survival. Of 92 patients, 24 (26.1%) underwent mastectomy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…9,17,28 However, a recent study reported no significant difference in overall survival between octogenarians and nonagenarians who did and did not receive adjuvant treatments for early-stage breast cancer. 30 Therefore, the lower rates of GCC observed among the oldest age groups of women may be reasonable, considering individual patient circumstances. Moreover, because of functional status, quality of life, and life expectancy, oncologists often cite increasing age, with or without comorbidity, as the primary reason for use of less aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,28 However, a recent study reported no significant difference in overall survival between octogenarians and nonagenarians who did and did not receive adjuvant treatments for early-stage breast cancer. 30 Therefore, the lower rates of GCC observed among the oldest age groups of women may be reasonable, considering individual patient circumstances. Moreover, because of functional status, quality of life, and life expectancy, oncologists often cite increasing age, with or without comorbidity, as the primary reason for use of less aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most frequent cancer among women, with psychological, professional, and social effects. 1 , 2 Diagnosis and treatment, as well the consequences on womanhood and everyday life, are often harsh. In this “hostile” environment, most women undergo breast surgery, which can lead to even more stress.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most frequent cancer among women, with psychological, professional, and social effects . Diagnosis and treatment, as well the consequences on womanhood and everyday life, are often harsh.…”
Section: Introductionmentioning
confidence: 99%